Incredible India - Trivedi, V. J. (Vidyapith (વિદ્યાપીઠ), 2010)
It is the book review article Title : Incredible India Author : Vyas, Rajani Publisher : Akshar Prakashan Pvt., Ltd., New Delhi Yera of Publication: 2008